Performance of solvent debinding using design of experiment method - Jamaludin, Khairur Rijal; Muhamad, Norhamidi; Rahman, M. N. A. B.; Amin, Sri Yulis M.; Ahmad, Sufizar; Ibrahim, Mohd. Halim Irwan; Murtadhahadi, Murtadhahadi (UKM, 2009)
Water leaching process has been widely accepted in Metal Injection Moulding (MIM) process based on its ability to enhance the debinding process. Soluble binder was extracted from the green body, which will develop pores that helped to increase thermal debinding rate. This paper presents the optimisation of the water leaching process using Taguchi method. The influence of the water leaching variables such as solvent temperature, particle size distribution, powder loading and injection pressure was discussed. Two types of SS316L powder were used in the experiment; gas atomised and water atomised powder. Results showed that solvent temperature played a very important role in the water leaching process when it contributes about 91.602% (for gas atomised powder) and 84.978% (for water atomised powder) to the binder extraction rate. However, powder particle size distribution only contributes 6.638% dan 12.228% for gas and water atomised powders, respectively to the binder extraction rate. Solvent tenperature demonstrated very high significant level, a = 0.005 for both powders. However the SS316L particle size distribution was moderately significant at a = 0.025, and a = 0.01 for both powder compact.